The study of the variation effect in the percent of the fibers in the gradients of composite materials on the percentage of water absorption of concrete beams when using 20% from the weight of cement in concrete beams - Babiker, Mohammed B. A.; Elarabi, Salaheldin M. (Gezira Journal of Engineering and Applied Sciences; Vol 17 No 2 (2022), 2026)
The use of the biocomposites for reinforce the concrete beams to improve their properties like bearing strength, strains, reducing from the errors of buildings, accordingly the aim from this study is avoid the error that resulting from the use of conventional  materials like wood(shortage in the strength from insect and fungi) and the steel(corrosion from rust) are used for reinforcing the concrete beams that by using composite materials from( kenaf fibers& metallic fibers ) of  samples (A,B,C) the percentage (67%&33% ” 50&,50% ” 33%&67%)  sequentially with the epoxy resin as connection material with hardener materials, Whereas the composite materials are used by 20% percentage  from the weight of the cement entire in the ingredient of concrete beams. That produced from these materials (cement, sand, concrete) in the mould for 24hour and then extracted from it and immersed in water tank for 7days&28day, then extracted from it and carry on it the percentage of water absorption  test. The results showing that, the percentage of water absorption of standard sample after 7days is 0.52% , So the best sample A with percentage of water absorption is 2.96%  and then C with percentage of water absorption is 1.87 and B with percentage of water absorption  is 1.15%  . As the result showing that the percentage of water absorption of standard sample after 28 day is 1.94%, So the best sample A with percentage of water absorption is 6.36%, Then C with percentage of water absorption is 3.25 and B with percentage of water absorption is 1.71 . إستخدام المواد المركبة الحيوية لتقوية الابيام الخرصانية يحسن خواصها كتحمل قوة الكسر والاجهادات والتقليل من اخطاء المباني , وفقا لذلك فأن  الهدف من هذه الدراسة هو تفادي العيوب الناتجة من استخدام المواد التقليدية كالخشب (ضعف القوة الناتجة من مهاجمة الفطريات والحشرات)  والاستيل (التأكل الناتج من الصدأ) في تقوية الابيام الخرصانية وذلك بإستخدام مواد مركبة من(الياف الكناف والالياف المعدنية) للعينات  بنسب(70% و30%& 50% و50% & 30% و 70%) علي التوالي مع راتنج الإيبوكسي  (C&B&A)  كمادة رابطة مع المادة المصلدة, حيث أستخدمت هذه المواد المركبة بنسبة 20% من وزن الاسمنت  الداخل في تركيبة الابيام الخرصانية  والتي أنتجت من المواد ( الاسمنت : الرمل : الخرصانة ) ، في قالب بابعاد     وتركت فيه لمدة  24ساعة ثم أستخرجت منه وغمرت في خزان مائي لمدة   {15cmx15cmx52.5cm} 7 إيام و28 يوم ثم استخرجت من الخزان المائي وأجري عليها اختبار نسبة الإمتصاصية، أظهرت النتائج المتحصلة إن نسبة الإمتصاصية للعينة القياسية بعد مرور 7 إيام هي 0.52 % وعليه فإن أفضل عينة هي   بنسبة إمتصاصية 1.15 % ،  B بنسبة إمتصاصية 1.78 % ثم C بنسبة إمتصاصية 2.96 % ، تليها   A     كما أظهرت النتائج إن نسبة الإمتصاصية للعينة القياسية بعد مرور 28 يوم هي 1.94 % وعليه أفضل عينة   بنسبة إمتصاصية 1.72 % .   B بنسبة إمتصاصية 3.25% ، ثم C بنسبة إمتصاصية 6.36% ، تليها A